Mindfulness Leadership in Education: Integrating Bibliometric Mapping and Thematic Synthesis - Rosnelly Barus; Winda Dewi Listyasari; Mohammad Sofwan Effendi; Kamaludin Kamaludin (Journal of Educational Sciences, 2026)
This study aims to synthesize and systematically map the growing body of research on mindfulness leadership in education published between 2019 and 2025, a period marked by increasing scholarly interest in well-being, ethical governance, and transformative practices in schools. Using a PRISMA-guided Systematic Literature Review, this study combines bibliometric mapping and reflexive thematic analysis to identify conceptual linkages, dominant themes, and emerging research directions. A total of 40 peer-reviewed articles across diverse educational settings were analysed. The synthesis reveals four major interconnected themes: contemplative pedagogy, ethical and compassionate leadership, teacher well-being, and organizational transformation through mindfulness. Findings show that mindfulness leadership fosters reflective awareness, relational trust, and emotional regulation among school leaders, which in turn strengthens teacher well-being and supports positive school climate. Evidence also suggests that mindfulness practices bridge personal contemplative development with systemic change, positioning leadership as both an internal capacity and an organizational influence. The review also identifies gaps, including limited empirical work in non-Western contexts and a need for longitudinal and mixed-method designs. The study concludes by proposing a conceptual model framing mindfulness leadership as a holistic and ethically grounded framework for cultivating resilient, emotionally intelligent, and values-driven educational environments.